Peran Logika dalam Pembelajaran Matematika: Pengenalan Konsep Pembuktian Sejak Awal - Miranti Miranti; Anggita Lutfia Ryawati; Hulva Sari; Salsa Ameylia Zahra; Abel Puspita Sari; Pera Santika; Muhammad Win Afgani (JURNAL RISET RUMPUN MATEMATIKA DAN ILMU PENGETAHUAN ALAM, 2025)
Logic is an important foundation in mathematics learning because it shapes critical and systematic thinking skills. Introducing the concept of proof early on plays a strategic role in developing reasoning skills, identifying patterns, and providing simple arguments. This article aims to examine the role of logic in mathematics learning by emphasizing the importance of introducing the concept of proof from the outset. The methods used are a literature review of various relevant studies and descriptive analysis based on learning practices in early childhood education. The results of the study show that play, exploration, and concrete experience-based learning activities can improve children's ability to understand cause-and-effect relationships, make predictions, and convey logical reasons. In addition, social interaction and dialogue in the learning process have been proven to strengthen simple reasoning skills. In conclusion, the integration of logic and reasoning from an early age not only supports the development of mathematical abilities, but also builds the foundation for critical and analytical thinking needed for further education.